Limits of functions – traces of students’ concept images - Juter, Kristina (NOMAD Nordic Studies in Mathematics Education, 2005)
Students at a Swedish university were subjects in a study about learning limits of functions. The students’ perceptions were investigated in terms of traces of concept images through interviews and problem solving. The results imply that most students’ foundations were not sufficiently strong for them to understand the concept of limit well enough to be able to form coherent concept images. The traces of the students’ concept images reveal confusion about different features of the limit concept.